Sound, syntax and contact in the languages of Asturias - Lorenzo González, Guillermo (Issues in Hispanic and Lusophone Linguistics Ser., 2022)
"This is the first generative-oriented volume ever published about Asturian and Asturian Galician, two Romance languages which, along with their intrinsic interest, are crucial to understand the parametric distance between Spanish and Galician/Portuguese. Its chapters offer new insights about old puzzles, like pronominal enclisis or apparent violations of bans on clitic combinatorics, but they also explore less explored grounds, like aspect, negation or prosody. Chapters make special emphasis on how the concerned issues result from complex interactions between syntax proper and its interfaces with sound and meaning. The book focuses on particular aspects of Asturian and Asturian Galician, as well as on some effects of their contact with Spanish in their corresponding locations"--